EFFECT OF OPERATING CASH FLOW, INVESTMENT CASH FLOW, FUNDING CASH FLOW AND NET PROFIT ON STOCK RETURN - Ezra Yesica br Pardede; Vania Chessy Angela Sihotang; Roma Asi Sinaga; Teng Sauh Hwee (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background Inflation is a continuous rise and fall in the price of goods or a situation where the price level of the economy tends to rise. When inflation rises, stock prices of income usually decrease. Method The method used in this study is a quantitative method using secondary data published by the IDX. Result The test results show that Interest Rates, Third Party Funds, Inflation, and Exchange Rates have a simultaneous effect on stock prices for the 2018-2020 period. Conclution From the results of the tests conducted on the eLevel of e-Interest, TPF, eInflation, and e-Exchange Rate of Stock Prices in the BEI Banking sub-sector for the period 2018-2020, it is known that these variables have a simultaneous effect.